Triarylamine‐Substituted Imidazole‐ and Quinoxaline‐Fused Push–Pull Porphyrins for Dye‐Sensitized Solar Cells. Issue 3 (11th February 2013) - Hayashi, Hironobu; Touchy, Abeda Sultana; Kinjo, Yuriko; Kurotobi, Kei; Toude, Yuuki; Ito, Seigo; Saarenpää, Hanna; Tkachenko, Nikolai V.; Lemmetyinen, Helge; Imahori, Hiroshi
Abstract We have prepared a push–pull porphyrin with an electron‐donating triarylamino group at the β, β′‐edge through a fused imidazole group and an electron‐withdrawing carboxyquinoxalino anchoring group at the opposite β, β′‐edge (ZnPQI) and evaluated the effects of the push–pull structure of ZnPQI on optical, electrochemical, and photovoltaic properties. ZnPQI showed red‐shifted Soret and Q bands relative to a reference porphyrin with only an electron‐withdrawing group (ZnPQ), thus demonstrating the improved light‐harvesting property of ZnPQI. The optical HOMO–LUMO gap was consistent with that estimated by DFT calculations. The ZnPQI‐sensitized solar cell exhibited a relatively high power conversion efficiency (η) of 6.8 %, which is larger than that of the ZnPQ‐sensitized solar cell (η=6.3 %) under optimized conditions. The short‐circuit current and fill factor of the ZnPQI‐sensitized solar cell are larger than those of the ZnPQ‐sensitized solar cell, whereas the open circuit potential of the ZnPQI‐sensitized cell is smaller than that of the ZnPQ‐sensitized cell, leading to an overall improved cell performance of ZnPQI. Such fundamental information provides a new tool for the rational molecular design of highly efficient dye‐sensitized solar cells based on push–pull porphyrins.